Se\~nales de inversión basadas en un índice de aversión al riesgo - Raúl Gómez Martínez; Jean-Pierre Lévy-Mangín (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
Internet searches statistics is a tool that is becoming more important in social science research. We propose to use the Internet search statistics, obtained through Google Insights, as an indicator of confidence or risk aversion of investors. Using this information we developed a Risk Aversion Index (RAI) from the volume of searches done on Google over certain economic or financial terms that are negatively correlated with the market trends. In this paper we show empirically through an econometric model that Google search statistics provide important information on the evolution of financial markets and the RAI provides investment signals with predictive power over the evolution of the main European stock index giving negative returns if the RAI increases and positive otherwise.
Keywords: C; G1; G2; 330; Investment signs; Expectations; Google Insights; Risk aversion; Investor's mood